2017
DOI: 10.1111/codi.13767
|View full text |Cite
|
Sign up to set email alerts
|

Defining low anterior resection syndrome: a systematic review of the literature

Abstract: LARS is common, but there is substantial variation in the reporting of functional outcomes after low anterior resection. Most studies have focused on incontinence, omitting other symptoms that correlate with patients' quality of life. To improve and standardize research into LARS, a consensus definition should be developed, and these findings should inform this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 43 publications
2
141
1
8
Order By: Relevance
“…Systematic review of literature published between 1986 and 2016 that reported functional outcomes after sphincter preserving rectal resection was undertaken to produce a comprehensive list of bowel function outcomes which were then tested in a pilot study. The results of this review have been published and were used in round 1 of the Delphi survey. Participants were invited to add novel items during round 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic review of literature published between 1986 and 2016 that reported functional outcomes after sphincter preserving rectal resection was undertaken to produce a comprehensive list of bowel function outcomes which were then tested in a pilot study. The results of this review have been published and were used in round 1 of the Delphi survey. Participants were invited to add novel items during round 1.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst pragmatic, this definition can incorporate a vast array of symptoms from faecal incontinence and urgency, to evacuation difficulties. Consequent heterogeneity in reporting makes it impossible to accurately identify the prevalence of LARS . Development of a validated patient‐reported outcome measure, the LARS score, has improved standardization of reporting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient representatives sent newsletters to maintain participant engagement and highlight the focus on the patient perspective. In each survey, participants were asked to rank each item on a 1-9 point Likert scale from 'Not important' (1) to 'Essential' (9) for the definition of LARS, with an additional response option 'Unable to comment' (0) (see Appendix S1 for the format of a question, http:// links.lww.com/DCR/B127). Likert rankings of 7-9 in any round were considered to indicate high-priority items, ratings of 4-6 indicated moderate-priority items that were important but not critical for the definition and rankings of 1-3 were low priority.…”
Section: Phase 1: Online Delphi Surveymentioning
confidence: 99%
“…In a multicenter cross-sectional study by the UK Low Anterior Resection Syndrome Study Group, Battersby et al showed that 85% of patients following curative restorative anterior resection reported bowel-related quality-of-life impairment, with 40% reporting major impairment [3]. A thorough assessment of LARS is complex employing 18 instruments and over 30 symptoms as reported by Keane et al [2] but most studies employ much simpler questionnaires. The most frequently reported outcomes were incontinence (97%), stool frequency (80%), urgency (67%), evacuatory dysfunction (47%), gas-stool discrimination (34%) and a general measure of quality of life (80%).…”
mentioning
confidence: 99%